Analisis Faktor yang Mempengaruhi Jumlah Penerimaan Zakat pada Baznas Tahun 2015- 2023 - Refi Emilia Svetlana; Nurhayadi, Yadi; Legowati, Diah Ayu (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2024)
This research aims to determine the effect of inflation, money supply, and minimum wage on the amount of zakat receipts at BAZNAS. This research uses quantitative research with ratio scale datas. The data collection technique method in this research is the documentation method which takes data reports on the official websites of Bank Indonesia, Badan Pusat Statistik, and Badan Amil Zakat Nasional from 2015 to 2023. The data analysis method for this research uses multiple linear regression analysis by carrying out classical assumption test and hypothesis testing. The data processing tool used is the Stata 17 program. The results of this research show that partially inflation has no significant effect on the amount of zakat receipts, the amount of money supply has a positive significant effect on the amount of zakat receipts, and the minimum wage has no significant effect on the amount of zakat receipts. Then, simultaneously the variables inflation, money supply, and minimum wage have a significant effect on the amount of zakat receipts.